Motor Imagery Combined With Physical Training Improves Response Inhibition in the Stop Signal Task - Son, Sung Min; Yun, Seong Ho; Kwon, Jung Won (Frontiers in Psychology, 2022)
Background: Motor imagery training has a similar effect to that of physical training on motor performance. The objective of this study was to investigate the short-term effectiveness of motor imagery training on response inhibition using the stop signal task (SST). Methods: Participants were divided into a physical training group (PT, n = 17), a motor imagery training group (MIT, n = 17), and a motor imagery combined with physical training group (MIPT, n = 17). All participants performed 10 SST training sessions over 5 days. Both stop signal reaction time (SSRT) and non-signal reaction time (NSRT) were measured before and after SST training. Results: There were significant interaction (time × group) and time effects, although the group effect was not statistically significant. Bonferroni post-hoc analysis showed that MIPT group revealed a significantly greater change in SSRT than PT and MIT groups, while there was no significant difference between PT and MIT groups. SSRT significantly decreased after training in all groups. In NSRT, there was a significant effect of time, but there was no significant interaction effect (time × group) or group effect. Conclusion: Response inhibition could be enhanced via training, and it was most effective when motor imagery and physical training were combined. We demonstrate that motor imagery training significantly improves response inhibition and should be accompanied by physical training when performing SST.